Applying OntoREM to a Space Mission: Developing Requirements for the MASCOT Lander. Issue 1 (2014) - Antonini, Kelly; Lange, Caroline; Kossmann, Mario; Odeh, Mohammed
Abstract OntoREM is an Ontology‐driven Requirements Engineering Methodology supported by software tooling, developed jointly by UWE and Airbus. OntoREM has been tested using a number of pilot cases in various domains at Airbus. In this research, OntoREM is applied to a space mission called MASCOT (Mobile Space Asteroid Scout) developed by DLR (Deutsches Zentrum für Luft‐ und Raumfahrt), Germany, together with CNES (Centre National d'Etudes Spatiales), France, and the Japanese Space Agency (JAXA). The research provided the opportunity to carry out a comparative critical evaluation of the outcomes of the application of OntoREM to MASCOT versus the outcomes of a more traditional Systems Engineering approach as applied by DLR‐Bremen. The key objective was to generate an alternative set of MASCOT requirements using OntoREM based on the existing set of MASCOT system requirements, and to compare the quality of the resulting requirements with the quality of the existing requirements in terms of correctness, completeness and consistency. The application of OntoREM to MASCOT has been successful, it appears that OntoREM is suitable for the development of requirements for space mission programmes and creates quality improvements when generating requirement specifications. About 100% additional project and system requirements were identified, while a re‐usable MASCOT project domain ontology was built during the process that may be generalised for future lander missions.